Reprogrammable sequencing for physically intelligent underactuated robots - Leon M. Kamp; Mohamed Zanaty; Ahmad Zareei; Benjamin Gorissen; Robert J. Wood; Katia Bertoldi (Proceedings of the National Academy of Sciences, 2025)
Programming physical intelligence into mechanisms holds great promise for machines that can accomplish tasks such as navigation of unstructured environments while utilizing a minimal amount of computational resources and electronic components. In this study, we introduce a design approach for physically intelligent underactuated mechanisms capable of autonomously adjusting their motion in response to environmental interactions. Specifically, multistability is harnessed to sequence the motion of different degrees of freedom in a programmed order. A key aspect of this approach is that this order can be passively reprogrammed through mechanical stimuli arising from interactions with the environment. To showcase our approach, we construct a mechanism that passively sorts objects based on their mass and a four-degree-of-freedom robot capable of autonomously moving away from obstacles. Remarkably, these devices operate without relying on traditional computational architectures and utilize only a single linear actuator.